Impact of Investment, Funding, and Profitability on Indonesian Manufacturing Firm Valuation - Kepramareni, Putu; Mirayani, Luh Putri Mas; Idayani, Ni Putu Tisha Manika (Jurnal Ekonomi dan Bisnis Jagaditha, 2024)
This research seeks to examine the impact of investment decisions, funding choices, dividend policies, company growth, and profitability on the valuation of manufacturing firms listed on the Indonesia Stock Exchange from 2020 to 2022. The analytical approach employed involves multiple linear regression analysis, utilizing annual data collected from manufacturing companies listed on the Indonesia Stock Exchange within the specified timeframe. The research sample consists of 135 selected entities determined through the purposive sampling method. The outcomes of the research reveal that investment decisions exert a negative impact on company value, whereas funding and profitability decisions demonstrate a positive influence on company value. However, dividend policy and company growth do not exhibit a statistically significant effect on company value. These results contribute to a more profound comprehension of the determinants shaping company value within the realm of manufacturing companies in Indonesia. This could serve as a reference for corporate managers when formulating strategic decisions to enhance their company's value. It is anticipated that future research endeavors may build upon this research by incorporating additional variables with potential impacts on company value, such as capital structure.